The Poor “Wealth” of Brazilian Football: How Poverty May Shape Skill and Expertise of Players - Uehara, Luiz; Falcous, Mark; Button, Chris; Davids, Keith; Araújo, Duarte; de Paula, Adelgício Ribeiro; Saunders, John (Frontiers in Sports and Active Living, 2021)
Worldwide, 1.3 billion people live in Poverty, a socio-economic status that has been identified as a key determinant of a lack of sports participation. Still, numerous athletes around the world have grown up in underprivileged socio-economic conditions. This is the case in Brazil, a country with around 13.5 million impoverished citizens, yet, over decades, many of its best professional footballers have emerged from its favelas. In this article, we explore the role of the socio-cultural-economic constraints in shaping the development of skill and expertise of Brazilian professional football players. The methodological and epistemological assumptions of the “Contextualized Skill Acquisition Research” (CSAR) approach are used as an underpinning framework for organizing and analyzing data. Results suggested that, at the exosystemic level of Brazilian society, Poverty emerges as an influential constraint that can potentially enrich football development experiences of Brazilian players. Poverty, however, is not the direct causation of outstanding football skill development. Rather, from the perspective of ecological dynamics, Poverty creates specific contexts that can lead to the emergence of physical as well as socio-cultural environment constraints (e.g., Pelada, Malandragem) that can shape affordances (opportunities) for skill acquisition. These ideas suggest the need to ensure that environmental constraints can support people to amuse themselves cheaply, gain access to employment opportunities and maintain health and well-being through (unstructured and more structured) sport and physical activities in dense urban environments such as favelas, inner city areas, and banlieues. For this purpose, design of open play areas and even parkour installations can provide affordances landscapes for physical activity and sports participation in urban settings.